A double-blinded, randomized, placebo-controlled trial assessing the effects of nifedipine on embryo transfer: Study protocol. Issue 51 (December 2017) - Ng, Kelvin KL; Rozen, Genia; Stewart, Tanya; Agresta, Franca; Polyakov, Alex
Abstract: Introduction: Implantation failure is the main factor affecting the success rate of in vitro fertilization (IVF) procedures. Studies have reported that uterine contractions (UCs) at the time of embryo transfer (ET) were inversely related to implantation and pregnancy rate, hence reducing the success of IVF treatment. Various pharmacological agents, with the exception of calcium channel blocker (CCB), have been investigated to reduce UC. In this regard, we are presenting a proposal for a double-blind randomized placebo-controlled trial. The trial aims to determine whether nifedipine, a CCB with potent smooth muscle relaxing activity and an excellent safety profile, can improve the outcome of ET. Methods and analyses: We will recruit 100 infertile women into one of 2 groups: placebo (n = 50) and nifedipine 20 mg (n = 50). Study participants will be admitted 30 minutes prior to ET and given either tablet after their baseline vital signs have been recorded. They will then undergo ET and be observed for adverse events for another 30 minutes post-ET. The primary outcome will be implantation rate and clinical pregnancy rate. Secondary outcomes include adverse events, miscarriage and pregnancy, and neonatal outcomes. Resulting data will then be analyzed using t test, Chi-square test, and multivariate test to compare outcomes between the 2 groups for any statistical significance. This protocol has been designed in accordance with the SPIRIT 2013 Guidelines.